Preparation method of graphene / copper-based composite material
Through the plasma-assisted ball milling method, nanographite powder is peeled off in situ into nanographene and recombined with copper powder, solving the problem that graphene is difficult to disperse uniformly in the copper matrix and is not strong in the interface, achieving high-performance graphene The preparation of /copper-based composite materials improves the strength-plasticity and electrical conductivity of the material.
Patent Information
- Application Number
- CN202310986960.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-08
- Publication Date
- 2025-02-18
AI Technical Summary
Graphene is difficult to disperse evenly in the copper matrix, and its interface with the copper matrix is not strong, resulting in the inability to fully exert its excellent performance.
Nanographite powder and spherical copper powder are used to achieve in-situ peeling into nanographene into nanographene through plasma-assisted ball milling method and compounding with copper powder. By adjusting the ball mill parameters, controlling the introduced oxygen group content, ensuring the structural integrity and intrinsic properties of graphene, achieving uniform dispersion of graphene in the copper matrix and improving the interfacial bonding strength.
The uniform dispersion of graphene in the copper matrix and the improvement of interface bonding strength, simultaneously improving the strength-plasticity and strength-conductive matching performance of the material, greatly reducing the cost of graphene, and is suitable for high-performance graphene/copper-based composite materials. macrosized preparation.
Smart Images

Figure CN119464812A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a graphene / copper-based composite material, and belongs to the technical field of preparation of metal-based composite materials. Background Art
[0002] Copper-based composites have excellent mechanical properties, such as strength, modulus and fracture toughness, as well as excellent thermophysical properties, such as thermal expansion coefficient, wear resistance and electrical conductivity, and are therefore widely used in aerospace, transportation and electronic communications. There are many types of reinforcing phases in metal-based composites, and traditional reinforcing phases are usually dominated by ceramic reinforcing phases, such as silicon carbide, aluminum oxide and titanium boride. Ceramic reinforcing phases usually have high hardness, strength, elastic modulus, wear resistance and low expansion coefficient, so introducing them into the metal matrix can significantly improve the corresponding properties of metal-based composites. However, the hard and brittle intrinsic properties of ceramic particles greatly reduce the secondary processing ability of composites. In addition, the electrical and thermal conductivity of ceramic particles is poor, and introducing them into the metal matrix will inevitably reduce the electrical and thermal conductivity of the composite material, which limits its further widespread application in the field of metal-based composites. Graphene has excellent electrical and thermal conductivity, mechanical properties and unique two-dimensional structure. As a reinforcement, it can theoretically improve the mechanical properties of the copper matrix without reducing or even improving the electrical and thermal conductivity of the composite material.
[0003] There are two main problems in using graphene as a reinforcement to prepare copper-based composites: 1) Due to the large specific surface area of graphene and the large difference between the density of graphene itself and the density of the copper matrix, graphene is easy to agglomerate, making it difficult to achieve uniform dispersion of graphene in the copper matrix, and the van der Waals force between graphene layers greatly reduces the strengthening effect of graphene; 2) Graphene and the copper matrix do not wet and do not react chemically, making it difficult for graphene and the copper matrix to form a good interface bond. At present, the methods developed for preparing graphene / copper composites include ball milling, electrostatic adsorption, molecular-level mixing, laminated composites, and in-situ growth. It is crucial to develop a method for preparing high-performance graphene / copper composites that is simple in process, low in cost, and can achieve uniform distribution of graphene in the copper matrix.
[0004] Patent CN201711201425.9 uses spherical copper powder as the matrix material and graphene as the reinforcing phase. Through the steps of graphene liquid phase dispersion, ball milling pre-dispersion, surface coating, hot isostatic pressing, hot extrusion, etc., a high-strength and high-conductivity graphene-reinforced copper-based composite material with nearly full density, good conductivity, high tensile strength, high hardness and high elongation is prepared. Its process is relatively complicated, and it is impossible to achieve uniform dispersion of graphene in the matrix, resulting in the inability to fully exert the excellent performance of graphene in the bulk material. Patent CN201910299341.6 grows graphene in situ by coating a polymer solid carbon source on the surface of copper powder, and then obtains a graphene / copper composite powder by ball milling. Its process is relatively complicated, and the graphene structure is greatly damaged, which greatly reduces the strengthening effect of graphene.
[0005] Patent 202011573401.8 uses plasma dry ball milling to evenly disperse graphene oxide and carbon nanotubes into aluminum alloy powder to obtain a composite powder, and then uses a fluidized bed to evenly disperse the short fibers into the mixed powder, further improving the strength of the composite material through mechanisms such as interface debonding and fiber breakage. The graphene and carbon nanotubes used in this process are relatively expensive and cannot be produced in large quantities. Summary of the invention
[0006] In view of the above problems, the present invention adopts nano-graphite powder and spherical copper powder through plasma-assisted ball milling method to realize in-situ exfoliation of nano-graphite powder into nano-graphene, as well as the composite of graphene and copper powder. By adjusting the ball milling parameters, the content of oxygen-containing groups introduced is regulated, the structural integrity and intrinsic properties of graphene during the composite process are effectively controlled, and the uniform dispersion of graphene in the copper matrix and the improvement of the bonding strength of the composite interface are achieved. On the one hand, the introduction of oxygen groups in-situ exfoliates nano-graphite powder into nano-graphene; on the other hand, while plasma-assisted ball milling refines the copper matrix grains, the uniform distribution of graphene in the copper matrix (intracrystalline) is achieved.
[0007] The technical solution of the present invention is to solve the above problems and propose a plasma-assisted ball milling method to prepare graphene / copper composite materials by in-situ exfoliation of nanographite powder into graphene. The process of the present invention is simple, effectively solves the problems of uniform dispersion of graphene and interface bonding with the copper matrix, greatly reduces the cost of graphene, is suitable for macro-quantitative preparation of high-performance graphene / copper-based composite materials, and establishes a macro-quantitative preparation technical route of "in-situ composite-hot pressing sintering-hot rolling".
[0008] To achieve the above object, the technical solution adopted by the present invention is:
[0009] A method for preparing a graphene / copper-based composite material, comprising the following steps:
[0010] Step 1, taking spherical copper powder and nano graphite powder respectively and placing them in a tube furnace in a reducing atmosphere for reduction treatment;
[0011] Step 2: Place the annealed spherical copper powder, nanographite powder and cemented carbide balls into a cylindrical stainless steel ball mill, evacuate the ball mill, and then fill it with high-purity argon and a small amount of air to obtain in-situ composite graphene / copper composite powders through plasma-assisted ball milling.
[0012] Step 3, placing the graphene / copper composite powder obtained after plasma-assisted ball milling in a tube furnace for reduction treatment under a reducing atmosphere;
[0013] Step 4: loading the graphene / copper composite powder into a circular graphite mold, and sintering in a rapid hot pressing sintering furnace to obtain a cylindrical block of the graphene / copper composite material;
[0014] Step 5: obtaining a graphene / copper composite material with matching strength-plasticity and strength-conductivity by hot rolling the graphene / copper composite cylindrical block with different deformation amounts.
[0015] The method for preparing the graphene / copper-based composite material as described above is characterized in that the particle size of the spherical copper powder used is 10um-0.3um.
[0016] The method for preparing the graphene / copper-based composite material as described above is characterized in that the reducing atmosphere is a H2 / Ar mixed atmosphere.
[0017] The method for preparing a graphene / copper-based composite material as described above is characterized in that the reduction conditions of the spherical copper powder and the graphene / copper composite powder are 300-450° C. and 2 h.
[0018] The method for preparing the graphene / copper-based composite material as described above is characterized in that the volume content of the added nano-graphite powder is 1 vol%-3 vol%.
[0019] The method for preparing the graphene / copper-based composite material as described above is characterized in that the ball-to-material ratio is 20:1.
[0020] The method for preparing a graphene / copper-based composite material as described above is characterized in that: the oxygen content in the ball mill is controlled to be 10 -3 -10 -2 ppm (If the oxygen content is too low, the nanographite powder cannot be effectively exfoliated; if the oxygen content is too high, the performance of the composite material will decrease and strength-plasticity matching cannot be achieved.).
[0021] The preparation method of a graphene / copper-based composite material as described above is characterized by: using a vibrating plasma ball mill at a speed of 1000-1200 rpm, generating a dielectric barrier discharge plasma at a frequency of 8-10 kHz, and treating for 10 to 30 hours to obtain an in-situ composite graphene / copper composite powder.
[0022] The method for preparing a graphene / copper-based composite material as described above is characterized in that rapid hot pressing sintering is carried out in an argon atmosphere, and the sintering temperature, pressure and insulation time are 800-900° C., 40-50 MPa and 10-60 min, respectively.
[0023] The method for preparing the graphene / copper-based composite material as described above is characterized in that the hot rolling temperature and deformation amount are 400-600° C. and 60-90% respectively.
[0024] The present invention uses nano-graphite powder and spherical copper powder through a plasma-assisted ball milling method to achieve in-situ exfoliation of nano-graphite powder into nano-graphene and composite of graphene and copper powder. The compressive stress applied by the grinding balls and the excitation of the plasma cause plastic deformation of the copper powder to refine the grains; the shear stress and a small amount of oxygen enable in-situ exfoliation of the nano-graphite powder into graphene. Compared with traditional high-energy ball milling, the grain refinement effect is more significant, the nano-graphite powder is in-situ exfoliated into graphene, the dispersion is more uniform and the interface bonding strength is higher, and the intracrystalline distribution of part of the graphene is achieved, which effectively alleviates the stress-strain concentration and simultaneously improves the strong plasticity of the material.
[0025] By adjusting the ball milling parameters and regulating the content of oxygen-containing groups introduced, the structural integrity and intrinsic properties of graphene during the composite process are effectively controlled, and the uniform dispersion of graphene in the copper matrix and the improvement of the bonding strength of the composite interface are achieved. On the one hand, the introduction of oxygen groups in situ exfoliates nanographite powder into nanographene; on the other hand, while plasma-assisted ball milling refines the copper matrix grains, the uniform distribution of graphene in the copper matrix (intracrystalline) is achieved. The process of the present invention is simple, and it effectively solves the problem of uniform dispersion of graphene and interface bonding with the copper matrix, achieves strength-plasticity and strength-conductivity matching, greatly reduces the cost of graphene, and is suitable for the macro-quantity preparation of high-performance graphene / copper-based composite materials.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] Appropriate oxygen group (10 -3 -10 -2ppm: if the oxygen content is too low, the nano-graphite powder cannot be effectively stripped; if the oxygen content is too high, the performance of the composite material will be reduced, and the strength-plasticity matching cannot be achieved. The introduction of in-situ stripping of nano-graphite powder into graphene can achieve the matching of strength and plasticity of the composite material; graphene is prepared by plasma ball milling with nano-graphite powder to achieve uniform dispersion of graphene in the copper matrix, saving the cost of graphene raw materials; the distribution of graphene in the crystal is achieved through plasma-assisted ball milling, and a good interface bonding is formed between graphene and the copper matrix.
[0028] The invention is simple and efficient, can prepare large-scale composite materials, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a scanned photo of the 10um spherical copper powder raw material in Example 1;
[0030] Figure 2 is a scanned photo of the spherical copper powder after plasma ball milling in Example 1;
[0031] Figure 3 is the Raman spectrum of the nanographite powder before and after ball milling in Example 1;
[0032] Figure 4 is a transmission photograph of the graphene / copper composite material after hot rolling in Example 1;
[0033] Table 1 Mechanical properties and electrical conductivity of the examples. DETAILED DESCRIPTION
[0034] The present invention is described in further detail below.
[0035] Example 1
[0036] A method for preparing a graphene / copper-based composite material, comprising the following steps:
[0037] Step 1, taking 200g of spherical copper powder with a diameter of 10um and nano-graphite powder (2vol%) respectively, placing them in a tube furnace, and reducing them at 300°C for 2h in a 5% H2 / Ar mixed atmosphere;
[0038] Step 2: Using a vibrating plasma ball mill, the annealed spherical copper powder, nanographite powder and cemented carbide balls are placed in a cylindrical stainless steel ball mill (ball-to-material mass ratio is 20:1), the ball mill is evacuated, and then filled with high-purity argon and a small amount of air. The vibration ball mill is performed at a speed of 1200 rpm, and a dielectric barrier discharge plasma is generated at a frequency of 10 kHz. The treatment lasts for 15 hours to obtain an in-situ composite graphene / copper composite powder.
[0039] Step 3, placing the graphene / copper composite powder obtained after plasma-assisted ball milling in a tube furnace and reducing it in a 5% H2 / Ar atmosphere at 450°C for 2h;
[0040] Step 4, loading the graphene / copper composite powder into a graphite mold with a diameter of 30 mm, hot pressing and sintering in a rapid sintering furnace under an argon atmosphere, 900° C., and 50 MPa, and heat preservation for 20 minutes to obtain a cylindrical block of graphene / copper composite material;
[0041] Step 5: By hot rolling the graphene / copper composite cylindrical block at 500° C. for 90%, the conductivity, strength and elongation of the graphene / copper composite cylindrical block were measured to be 93% IACS, 360 MPa and 5% respectively.
[0042] Example 2
[0043] A method for preparing a graphene / copper-based composite material, comprising the following steps:
[0044] Step 1, taking 200g of 1um diameter spherical copper powder and nanographite powder (2.5vol%) respectively, placing them in a tube furnace, and reducing them at 300℃ for 2h in a 5% H2 / Ar mixed atmosphere;
[0045] Step 2: Using a vibrating plasma ball mill, the annealed spherical copper powder, nanographite powder and cemented carbide balls are placed into a cylindrical stainless steel ball mill (the ball-to-material mass ratio is 20:1), the ball mill is evacuated, and then filled with high-purity argon and a small amount of air (10 -2 ppm). The vibration ball milling was carried out at a speed of 1200 rpm, and the dielectric barrier discharge plasma was generated at a frequency of 10 kHz. The treatment lasted for 15 hours to obtain in-situ composite graphene / copper composite powders.
[0046] Step 3, placing the graphene / copper composite powder obtained after plasma-assisted ball milling in a tube furnace and reducing it in a 5% H2 / Ar atmosphere at 450°C for 2h;
[0047] Step 4, loading the graphene / copper composite powder into a graphite mold with a diameter of 30 mm, hot pressing and sintering in a rapid sintering furnace under an argon atmosphere, 900° C., and 50 MPa, and heat preservation for 20 minutes to obtain a cylindrical block of graphene / copper composite material;
[0048] Step 5: By hot rolling the graphene / copper composite cylindrical block at 500° C. for 90%, the conductivity, strength and elongation of the graphene / copper composite cylindrical block were measured to be 92% IACS, 380 MPa and 7% respectively.
[0049] Example 3
[0050] A method for preparing a graphene / copper-based composite material, comprising the following steps:
[0051] Step 1, taking 200g of 1um diameter spherical copper powder and nano graphite powder (2vol%) respectively, placing them in a tube furnace, and reducing them at 300°C for 2h in a 5% H2 / Ar mixed atmosphere;
[0052] Step 2: Using a vibrating plasma ball mill, the annealed spherical copper powder, nanographite powder and cemented carbide balls are placed into a cylindrical stainless steel ball mill (the ball-to-material mass ratio is 20:1), the ball mill is evacuated, and then filled with high-purity argon and a small amount of air (10 -3 ppm). The vibration ball milling was carried out at a speed of 1200 rpm, and the dielectric barrier discharge plasma was generated at a frequency of 10 kHz. The treatment lasted for 15 hours to obtain in-situ composite graphene / copper composite powders.
[0053] Step 3, placing the graphene / copper composite powder obtained after plasma-assisted ball milling in a tube furnace and reducing it in a 5% H2 / Ar atmosphere at 450°C for 2h;
[0054] Step 4, loading the graphene / copper composite powder into a graphite mold with a diameter of 30 mm, hot pressing and sintering in a rapid sintering furnace under an argon atmosphere, 900° C., and 50 MPa, and heat preservation for 20 minutes to obtain a cylindrical block of graphene / copper composite material;
[0055] Step 5: By hot rolling the graphene / copper composite cylindrical block at 500° C. for 75%, the conductivity, strength and elongation of the graphene / copper composite cylindrical block were measured to be 85% IACS, 460 MPa and 16% respectively.
[0056] Example 4
[0057] A method for preparing a graphene / copper-based composite material, comprising the following steps:
[0058] Step 1, taking 200g of 1um diameter spherical copper powder and nano graphite powder (2vol%) respectively, placing them in a tube furnace, and reducing them at 300°C for 2h in a 5% H2 / Ar mixed atmosphere;
[0059] Step 2: Using a vibrating plasma ball mill, the annealed spherical copper powder, nanographite powder and cemented carbide balls are placed into a cylindrical stainless steel ball mill (the ball-to-material mass ratio is 20:1), the ball mill is evacuated, and then filled with high-purity argon and a small amount of air (10 -3 ppm). The vibration ball milling was carried out at a speed of 1200 rpm, and the dielectric barrier discharge plasma was generated at a frequency of 10 kHz. The treatment lasted for 15 hours to obtain in-situ composite graphene / copper composite powders.
[0060] Step 3, placing the graphene / copper composite powder obtained after plasma-assisted ball milling in a tube furnace and reducing it in a 5% H2 / Ar atmosphere at 450°C for 2h;
[0061] Step 4, loading the graphene / copper composite powder into a graphite mold with a diameter of 30 mm, hot pressing and sintering in a rapid sintering furnace under an argon atmosphere, 900° C., and 50 MPa, and heat preservation for 20 minutes to obtain a cylindrical block of graphene / copper composite material;
[0062] Step 5: By hot rolling the graphene / copper composite cylindrical block at 500° C. for 90%, the conductivity, strength and elongation of the graphene / copper composite cylindrical block were measured to be 84% IACS, 500 MPa and 10% respectively.
[0063] Example 5
[0064] A method for preparing a graphene / copper-based composite material, comprising the following steps:
[0065] Step 1, taking 200g of 1um diameter spherical copper powder and nanographite powder (2.5vol%) respectively, placing them in a tube furnace, and reducing them at 300℃ for 2h in a 5% H2 / Ar mixed atmosphere;
[0066] Step 2: Using a vibrating plasma ball mill, the annealed spherical copper powder, nanographite powder and cemented carbide balls are placed into a cylindrical stainless steel ball mill (the ball-to-material mass ratio is 20:1), the ball mill is evacuated, and then filled with high-purity argon and a small amount of air (10 -2 ppm). The vibration ball milling was carried out at a speed of 1200 rpm, and the dielectric barrier discharge plasma was generated at a frequency of 10 kHz. The treatment lasted for 25 hours to obtain in-situ composite graphene / copper composite powders.
[0067] Step 3, placing the graphene / copper composite powder obtained after plasma-assisted ball milling in a tube furnace and reducing it in a 5% H2 / Ar atmosphere at 450°C for 2h;
[0068] Step 4, loading the graphene / copper composite powder into a graphite mold with a diameter of 30 mm, hot pressing and sintering in a rapid sintering furnace under an argon atmosphere, 900° C., and 50 MPa, and heat preservation for 20 minutes to obtain a cylindrical block of graphene / copper composite material;
[0069] Step 5: By hot rolling the graphene / copper composite cylindrical block at 500° C. for 90%, the conductivity, strength and elongation of the graphene / copper composite cylindrical block were measured to be 83% IACS, 560 MPa and 8% respectively.
[0070] Table 1. Mechanical properties and electrical conductivity of the examples
[0071]
[0072]
Claims
1. A method for preparing a graphene / copper-based composite material, characterized in that include: Step 1, taking spherical copper powder and nano graphite powder respectively and placing them in a tube furnace in a reducing atmosphere for reduction treatment; Step 2: Place the annealed spherical copper powder, nanographite powder and cemented carbide balls into a cylindrical stainless steel ball mill, evacuate the ball mill, and then fill it with high-purity argon and a small amount of air to obtain in-situ composite graphene / copper composite powders through plasma-assisted ball milling. Step 3, placing the graphene / copper composite powder obtained after plasma-assisted ball milling in a tube furnace for reduction treatment under a reducing atmosphere; Step 4: loading the graphene / copper composite powder into a circular graphite mold, and sintering in a rapid hot pressing sintering furnace to obtain a cylindrical block of the graphene / copper composite material; Step 5: obtaining a graphene / copper composite material with matching strength-plasticity and strength-conductivity by hot rolling the graphene / copper composite cylindrical block with different deformation amounts.
2. The method for preparing a graphene / copper-based composite material according to claim 1 is characterized in that: The particle size of the spherical copper powder used is 0.3um-10um.
3. The method for preparing a graphene / copper-based composite material according to claim 1 is characterized in that: The reducing atmosphere was a H2 / Ar mixed atmosphere.
4. The method for preparing a graphene / copper-based composite material according to claim 1 is characterized in that: The reduction conditions of spherical copper powder and graphene / copper composite powder are 300-450° C. and 1-4 h.
5. The method for preparing a graphene / copper-based composite material according to claim 1 is characterized in that: The volume content of the added nano graphite powder is 1 vol%-3 vol%.
6. The method for preparing a graphene / copper-based composite material according to claim 1 is characterized in that: The ball-to-material ratio is 20:
1.
7. The method for preparing a graphene / copper-based composite material according to claim 1 is characterized in that: Control the oxygen content in the ball mill to 10 -3 -10 -2 ppm.
8. The method for preparing a graphene / copper-based composite material according to claim 1 is characterized in that: A vibrating plasma ball mill is used to generate dielectric barrier discharge plasma at a speed of 1000-1200 rpm and a frequency of 8-10 kHz. The treatment lasts for 10-30 hours to obtain in-situ composite graphene / copper composite powder.
9. The method for preparing a graphene / copper-based composite material according to claim 1 is characterized in that: Rapid hot pressing sintering is carried out in an argon atmosphere, and the sintering temperature, pressure and holding time are 800-900°C, 40-50MPa and 10-60min respectively.
10. The method for preparing a graphene / copper-based composite material according to claim 1 is characterized in that: The hot rolling temperature and deformation amount are 400-600°C and 60-90% respectively.
Citation Information
Patent Citations
High-strength and high-conductivity graphene reinforced copper matrix composite material, preparation method and application thereof
CN108145169A
Preparation method of graphene copper-based composite material based on in-situ synthesis
CN110125385A
Graphene oxide and carbon nanotube reinforced aluminum-based composite material and preparation method thereof
CN114686786A
Cited By
A three-stage gradient heat preservation sintering preparation method of graphene copper composite blank
CN122955930A